Management of facial asymmetry due to overgrowing costochondral graft: A case report. (2016) - Razzak, Arif; Ahmed, Nabeela; Sidebottom, Andrew
Highlights: Costochondral grafts are the gold standard in TMJ replacement in growing patients. On occasion, growth in these grafts can sometimes be unpredictable, resulting in facial asymmetry. Careful surgical planning is required to ensure that correction of facial asymmetry does not affect the long term function of the temporomandibular joint. Abstract: Costochondral grafts are used to replace the mandibular condyle in cases of TMJ ankylosis, and are generally viewed as a gold standard for autogenous reconstruction of the mandibular condyle (Güven, 2000; Posnick and Goldstein, 1993 [1, 2]). We report a case where overgrowth of costochondral grafts is seen, resulting in asymmetric mandibular growth and dentofacial asymmetry (Posnick and Goldstein, 1993 [2]). A 17 year old male patient presented with an existing costochondral graft performed due to TMJ ankylosis during childhood. He fell from a height at the age of 4, and was lost to follow up through non-attendance until the age of 9, when he presented with a progressive reduction in maximal incisal opening (MIO). At this stage his maximal incisal opening was noted to be 11 mm, and the CT showed a grossly deformed ankylosed left TMJ. This post traumatic ankyloses was managed with gap arthroplasty and costochondral graft reconstruction. This immediately improved his MIO to 22 mm and at 1 year follow up was noted to be 30 mm. At age 12 he was noted to have a clinically obvious overgrowth of the left ramus of the mandible, and deviation of the chin point to the right. MIO remained at 38 mm. He declined orthognathic surgery and represented 2 years later requesting treatment without orthodontic intervention for his facial asymmetry. He subsequently underwent a Le Fort 1 impaction osteotomy, right BSSO and left condylar ostectomy, coronoidectomy and left lower border mandibulectomy. Regrowth of the CCG occurred during the 6 months of follow up. This case illustrates the problems that can occur after condylar trauma. It also highlights issues with costochondral grafts which can continue to grow.